Association between distance from the medial edges of the rectus abdominis and low back pain in college students - Custodio, Norma Myrella Saavedra (2023)
Introduction: Chronic low back pain in university students ranges between 12.4 and 75 %. It was initially evidenced that the alteration of the musculature of the rectus abdominis may be associated with low back pain. Objective: To evaluate the association between the distance from the medial edges of the rectus abdominis muscle and the presence of low back pain. Methods: A case-control study was conducted in students of a private university in the city of Lima. Low back pain and the distance between the medial edges of the rectus abdominis muscle were assessed using the numerical pain scale, the waist-hip index, the Nordic questionnaire and the Oswestry scale. The distance between the medial edges of the rectus abdominis muscle was measured with a digital Caliper. Results: The mean and standard deviation of the distance from the rectus abdominis was 21.9 ± 3.5. This and abdominal diastasis were associated with low back pain. Conclusions: The distance between the medial edges of the rectus abdominis muscle and low back pain in university students was shown to be related.